2015
DOI: 10.1183/13993003.00676-2015
|View full text |Cite
|
Sign up to set email alerts
|

Circulating free DNA concentration is an independent prognostic biomarker in lung cancer

Abstract: @ERSpublications Total cell-free DNA is not associated with chemotherapy response in advanced nonsmall cell lung cancer http://ow.ly/Qpqyx ABSTRACT Plasma circulating cell-free (cf)DNA is of interest in oncology because it has been shown to contain tumour DNA and may thus be used as liquid biopsy. In nonsmall cell lung cancer (NSCLC), cfDNA quantification has been proposed for the monitoring and follow-up of patients. However, available studies are limited and need to be confirmed by studies with larger sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
108
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 26 publications
12
108
2
2
Order By: Relevance
“…Three courses from three separate patients had missing PS, and PS was imputed as the mean PS value for all courses in the model. Total cell-free DNA level (TP53TAC) was included in the multivariable model because it has been reported as a possible independent prognostic marker in ovarian and other cancers [37,38]. …”
Section: Methodsmentioning
confidence: 99%
“…Three courses from three separate patients had missing PS, and PS was imputed as the mean PS value for all courses in the model. Total cell-free DNA level (TP53TAC) was included in the multivariable model because it has been reported as a possible independent prognostic marker in ovarian and other cancers [37,38]. …”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies had investigated the predictive or prognostic value of cfDNA concentration in NSCLC patients in recent years [1922] (see Table 1 for references). However, these studies were often small and reported varying results.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent large meta-analysis, a high correlation between ccfDNA concentration and mCRC patient survival was observed, revealing that patients with relatively low levels of ccfDNA lived significantly longer than patients with higher levels (6). The relevance of ccfDNA levels for the prognosis of other cancer types has also been described, including advanced breast cancer (10), lung cancer (11,12), prostate cancer (13), pancreatic cancer (14), and other cancer types (15).…”
Section: Introductionmentioning
confidence: 99%